AJARAN PENGENDALIAN DIRI DALAM TEKS GEGURITAN LEBUR CORAH - I Nyoman Suka Ardiyasa (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2023)
Geguritan is one of the traditional literary works that still exists in the midst of society as a medium for internalizing the teachings of Hinduism contained therein. One geguritan rich in self-control values is Corah's Geguritan Lebur which is a geguritan manuscript in the collection of the Bali Documentation Center. Geguritan is in the form of a pupuh which tells of a giant character who exercises more self-control than the gods. This article reviews in depth the Geguritan Lebur Corah script from the perspective of the values of self-control contained therein. The method used in preparing this article follows the steps of text research in general. According to the study conducted, geguritan melt corah contains the teachings of self-control. This can be observed in several main characters in geguritan who routinely practice yoga in the forest, even though they are giants. Through yoga and self-control, all the impurities that cling to it have been purged, just as the six enemies within oneself have been controlled. The goal of Hinduism, according to Geguritan Lebur Corah, is to achieve moksartham jagadhita ya ca iti dharma, or moksha and the welfare of mankind. It is impossible for humans to attain moksha if they cannot free themselves from karmaphala, or worldly bonds, and from samsara, or rebirth.Keywords: self control, geguritan lebur corah.